Loading SnS2 nanosheets decorated with MoS2 nanoparticles on a flake-shaped g-C3N4 network for enhanced photocatalytic performance. Issue 26 (17th June 2021) - Chen, Changzhao; Zang, Jiyuan; Wang, Qian; Li, Yuanzhi
Abstract : A g-C3 N4 /MoS2 /SnS2 ternary composite photocatalyst with a unique photo-generated carrier transfer pathway is obtained, which exhibits excellent photocatalytic activity. Abstract : Despite the significant amount of research in the field of graphitic carbon nitride (g-C3 N4 ) photocatalysis, there is still a long way to develop a g-C3 N4 -based composite photocatalyst with high visible light utilization, multiple active sites, and outstanding carrier separation and transfer efficiency, which are the key factors to obtain high photocatalytic performance. To address these goals, a ternary g-C3 N4 /MoS2 /SnS2 heterojunction was successfully fabricated for the first time by loading SnS2 nanosheets dotted with MoS2 nanoparticles on a flake-shaped g-C3 N4 network. The influence of different SnS2 /MoS2 contents on the photocatalytic efficiency of the hybrid photocatalyst has been investigated. The results revealed that the ternary composite with a SnS2 /MoS2 mass ratio of 20% exhibited the best photocatalytic activity. The degradation rate of rhodamine B reaches 100% within 60 min and the adsorption rate was less than 20%, with the overall performance being significantly superior to many composite photocatalysts based on g-C3 N4 reported in recent literature reports. The increase in activity should be attributed to the improvement in visible light absorption, the increase in active sites introduced by the exposed edges of MoS2 nanoparticles, and the effective charge separation and transfer arising from a unique photo-generated carrier transfer pathway different from the common type II or type Z schemes. The current ternary composite photocatalyst not only exhibited outstanding photocatalytic performance, but also had excellent cycle stability, thus indicating a bright application prospect.